Behavioral aspects of tax amnesties and their effects in twelve countries - ERDOĞDU, MUAMMER MUSTAFA (My University, 2022)
This paper overviews the theoretical and empirical research on tax amnesties and weighs their advantages and disadvantages. The paper questions if tax amnesties have any tax compliance impacts in the medium to long term as some papers have claimed or if they are more of a hindrance to tax compliance because of their unjust and degenerating effects. The paper examines the available data for the effects of tax amnesty programs on the ratio of tax revenues to GDP and the Gini coefficient for 12 countries focusing specifically on Turkey. The main aim of the paper is to identify better alternatives to tax amnesties in terms of both tax revenue and tax justice. The results of the study show that while the short-term revenue effect of tax amnesties is uncertain, their medium and long-term negative effects on tax justice and income distribution are almost certain. In addition, the study reveals that improving tax revenue is hardly the main reason behind most tax amnesties.
Keywords: Sosyal ve Beşeri Bilimler; Çalışma Ekonomisi ve Endüstri ilişkileri; Çalışma Ekonomisi; Social Sciences and Humanities; Labor Economics and Industrial Relations; Labor Economics; İŞ FİNANSI; Ekonomi ve İş; Sosyal Bilimler (SOC); BUSINESS, FINANCE; ECONOMICS & BUSINESS; Social Sciences (SOC); Finans; Muhasebe; İşletme, Yönetim ve Muhasebe (çeşitli); Sosyal Bilimler ve Beşeri Bilimler; Finance; Accounting; Business, Management and Accounting (miscellaneous); Social Sciences & Humanities; Tax amnesties; tax compliance; tax evasion; tax justice; Turkey; Tax amnesties; tax compliance; tax evasion; tax justice; Turkey